Mental health problems among the survivors in the hard-hit areas of the Yushu earthquake. - Zhen Zhang; Wenzhong Wang; Zhanbiao Shi; Li Wang; Jianxin Zhang (PLoS ONE, 2012)
BACKGROUND: On April 14, 2010, an earthquake registering 7.1 on the Richter scale shook Qinghai Province in southwest China. The earthquake caused numerous casualties and much damage. The epicenter, Yushu County, suffered the most severe damage. As a part of the psychological relief work, the present study evaluated the mental health statuses of the people affected and identified the mental disorder risk factors related to earthquakes. METHODS: Five hundred and five earthquake survivors living in Yushu County were investigated 3-4 months after the earthquake. Participant demographic data including gender, age, marital status, ethnicity, educational level, and religious beliefs were collected. The Earthquake-Specific Trauma Exposure Indicators assessed the intensity of exposure to trauma during the earthquake. The PTSD Checklist-Civilian version (PCL-C) and the Hopkins Symptoms Checklist-25 (HSCL-25) assessed the symptoms and prevalence rates of probable Posttraumatic Stress Disorder (PTSD) as well as anxiety and depression, respectively. The Perceived Social Support Scale (PSSS) evaluated subjective social support. RESULTS: The prevalence rates of probable PTSD, anxiety, and depression were 33.7%, 43.8% and 38.6%, respectively. Approximately one fifth of participants suffered from all three conditions. Individuals who were female, felt initial fear during the earthquake, and had less social support were the most likely to have poor mental health. CONCLUSIONS: The present study revealed that there are serious mental problems among the hard-hit survivors of the Yushu earthquake. Survivors at high risk for mental disorders should be specifically considered. The present study provides useful information for rebuilding and relief work.